2008
DOI: 10.1038/ncpendmet0894
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenesis of diabetic nephropathy

Abstract: Between 20% and 40% of patients with diabetes ultimately develop diabetic nephropathy, which in the US is the most common cause of end-stage renal disease requiring dialysis. Diabetic nephropathy has several distinct phases of development and multiple mechanisms contribute to the development of the disease and its outcomes. This Review provides a summary of the latest published data dealing with these mechanisms; it focuses not only on candidate genes associated with susceptibility to diabetic nephropathy but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
398
1
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 544 publications
(428 citation statements)
references
References 77 publications
9
398
1
12
Order By: Relevance
“…2007; Dronavalli et al. 2008). In the present study, the DM rats showed higher daily excretion of albumin and total protein compared with control rats.…”
Section: Discussionmentioning
confidence: 99%
“…2007; Dronavalli et al. 2008). In the present study, the DM rats showed higher daily excretion of albumin and total protein compared with control rats.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 As shown in Figure 4, A and B, GBM thickness increased significantly in the diabetic WT mice but did not change in the diabetic TxNIP KO. Similarly, effacement of the podocyte foot processes was observed only in the diabetic WT mice (Figure 4, A and C).…”
Section: Lack Of Txnip Protects Mice From Diabetes-induced Renal Fibrmentioning
confidence: 96%
“…2,30,31 Current attempts to normalize glycemia, control BP, and maintain blockade of the renin-angiotensin system have not eliminated DN or the need for dialysis and/or renal transplantation. 2,30,31 Thus, it is essential to identify novel drug targets and more effective therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress plays a causal role in DN62 (Figure 2). The main sources of superoxide in the kidney are the NOX enzymes, specifically the homologs NOX4 and NOX5, the latter only present in humans 63.…”
Section: Diabetic Nephropathy Antioxidant Defences and Immunotherapiesmentioning
confidence: 99%